A triglyceride-rich lipoprotein environment exacerbates renal injury in the accelerated nephrotoxic nephritis model - Saja,M; Cook,HT; Ruseva,M; Szajna,M; Pickering,MC; Woollard,KJ; Botto,M (Clinical and Experimental Immunology, 2018)
Hyperlipidaemia accompanies chronic renal disease either as a consequence of the renal dysfunction or as part of generalized metabolic derangements. Under both situations, the lipid profile is characterized by accumulation of triglyceriderich lipoproteins (TGRLs). This lipid profile is recognized as a risk factor for cardiovascular complications. Whether it may pose a risk for renal injury as well remains unclear. A hyperTGRL state was generated in C57BL/6 mice using poloxamer407 (P407) and immune complexmediated renal injury was triggered using the accelerated nephrotoxic nephritis (ANTN) model. The hyperTGRL animals were hypersensitive to ANTN demonstrated by greater haematuria and glomerular cellularity. These changes were accompanied by increased glomerular accumulation of CD68+ macrophages. The hypersensitive response to ANTN was not seen in lowdensity lipoprotein receptor knockout mice fed with a high fat diet, where triglyceride levels were lower but cholesterol levels comparable to those obtained using P407. These data indicate that a hyperTGRL state might be more detrimental to the kidneys than lowdensity lipoproteindriven hypercholesterolaemia during immune complexmediated nephritis. We speculate that the hyperTGRL environment primes the kidney to exacerbated renal damage following an inflammatory insult with increased accumulation of macrophages that may play a key role in mediating the injurious effects.